2020
DOI: 10.1186/s12967-020-02215-0
|View full text |Cite
|
Sign up to set email alerts
|

A clinical-radiomics nomogram for the preoperative prediction of lymph node metastasis in colorectal cancer

Abstract: Background: Accurate lymph node metastasis (LNM) prediction in colorectal cancer (CRC) patients is of great significance for treatment decision making and prognostic evaluation. We aimed to develop and validate a clinicalradiomics nomogram for the individual preoperative prediction of LNM in CRC patients. Methods:We enrolled 766 patients (458 in the training set and 308 in the validation set) with clinicopathologically confirmed CRC. We included nine significant clinical risk factors (age, sex, preoperative ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 26 publications
4
60
0
Order By: Relevance
“…The first article used a neural network to develop prediction models in head and neck cancer [ 23 ]. The second article developed a radiomics model based on CT images of colorectal cancer patients [ 24 ]. Both studies showed that there is potential by delineating lymph nodes for radiomics and deep learning analysis for the classification of positive and negative lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The first article used a neural network to develop prediction models in head and neck cancer [ 23 ]. The second article developed a radiomics model based on CT images of colorectal cancer patients [ 24 ]. Both studies showed that there is potential by delineating lymph nodes for radiomics and deep learning analysis for the classification of positive and negative lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a combination of clinical risk factors and radiomics features emphasized potential advantages to the individualized preoperative prediction of lymph node metastasis in CRC patients, which was proposed to benefit patient OS. Sun et al argued that the fibrinogen and neutrophil‐to‐lymphocyte ratio (F‐NLR score) is a promising predictor for disease relapse in rectal cancer patients 25,26 . The dissertations mentioned above were dedicated to predicting the preoperative or postoperative conditions of patients, and both might improve the prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The general consensus exists that the postoperative specimens of radical operations for colon cancer should contain at least 12 regional lymph nodes, as recommended by the National Comprehensive Cancer Network (NCCN) guidelines [ 2 ]. However, previous research indicated that young patients with colorectal cancer suffered a higher risk of lymph node metastasis [ 23 ]. Is a minimum of 12 RNE adequate for EOLACC?…”
Section: Discussionmentioning
confidence: 99%